Analysis of composite concrete steel column using “X” shape steel section - Ahmad Zeyad Abu Sharea; Shideh Shadravan (Heliyon, 2024)
In this paper, a new structural steel shape is proposed to be used in composite columns. The model is made of a concrete column with the proposed steel section embedded in concrete with four angles “L shape”, welded together to form the shape “X”. The equivalent compressive strength capacity of this “X” shape was compared to the conventional steel “W shape” section. The main goal of the research is the strength enlargement of composite columns.Three 6 ft long columns were analyzed: one conventional “W” section (W100 × 330), one with two angles (2 L 89 × 76.5 × 8), and one with four angles (4 L 50 × 50 × 6.5). Finite element analysis was completed using ABAQUS software and theoretical analysis was performed using AISC and Eurocode4. The deflection control analysis using ABAQUS was validated first on samples from a previously published experimental study conducted in the laboratory, and results from ABAQUS were aligned with the experimental study outcomes.This study found that the proposed “X” shape steel section has comparable compressive strength values to the conventional “W” section.